Selective CO2 and H-2 adsorption in a chiral magnesium-based metal organic framework (Mg-MOF) with open metal sites - Mallick, Arijit; Saha, Subhadeep; Pachfule, Pradip; Roy, Sudip; Banerjee, Rahul (Journal of Materials Chemistry, 2010)
A rare porous magnesium-based metal-organic framework, Mg-MOF-1 [Mg(3,5-PDC)(H2O)], was synthesized solvothermally in DMF. Structural determination by X-ray single-crystal diffraction technique reveals that this chiral MOF (space group P6(1)22) is constructed by helical assembly of Mg2+ ions with achiral 3,5-pyridine dicarboxylates and coordinating water molecules, to form a three-dimensional framework with parallel hexagonal channels. The structural detail of its 0D analogue Mg-MOF-2 [Mg(2,4-PDC)(H2O)(3)] has been discussed to show how subtle variation in the ligand architecture changes the resulting structure from 0D to 3D. Mg-MOF-1 remains robust and porous upon evacuation of the coordinating water molecules. This is the first report of a chiral hexagonal Mg-MOF synthesized from an achiral organic building unit. Open Mg metal sites show selective hydrogen (H-2) adsorption (ca. 0.8 wt% at 77 K) and carbon dioxide (CO2) uptake (ca. 0.7 mmol g(-1) at 298 K) over nitrogen at 1 atm. Ab initio quantum chemical calculation of adsorption energies and possible adsorption sites of hydrogen molecules are also reported.

Structure and gas sorption behavior of a new three dimensional porous magnesium formate - Mallick, Arijit; Saha, Subhadeep; Pachfule, Pradip; Roy, Sudip; Banerjee, Rahul (Inorganic Chemistry, 2011)
A new three-dimensional magnesium formate polymorph, namely, gamma-[Mg-3(O2CH)(6)] has been synthesized via in situ formate anion generation method. gamma-Mg-formate crystallizes in space group Pbcn, and structural determination by X-ray single crystal diffraction reveals a three-dimensional network of Mg2+ linked by formate anions. All formate anions possess similar binding mode to the metal center with one oxygen of a particular formate anion binds to one metal center (mu(1) oxygen) and other oxygen binds to two metal centers (mu(2) oxygen). N-2 adsorption studies indicate that the framework displays permanent porosity. The specific surface area of gamma-Mg-formate (BET, 120 m(2) gm(-1)) is lower than the alpha- polymorph (BET, 150 m(2) gm(-1)). However, the initial hydrogen uptake of gamma-Mg-formate reached almost 1.0 wt % when the adsorbate pressure approached 760 Torr at 77 K. This is higher than the hydrogen uptake of alpha-Mg-formate (0.6 wt %). gamma-Mg-formate, shows a moderate affinity and capacity for CO2 (3.4 angstrom kinetic diameter) at 298 K. The CO2 uptake at 760 Torr is 2.01 mmol gm(-1)(47.0 cc gm(-1)). Although this CO2 uptake is somewhat modest, it compares well with the CO2 uptake of several Mg-MOFs and ZIFs reported in the literature.

Structural, dynamical, and thermodynamical properties of carbon nanotube polycarbonate composites: a molecular dynamics study - Chakraborty, Souvik; Roy, Sudip (Journal of Physical Chemistry B, 2012)
All-atom molecular dynamics simulations are performed on pure monomer and trimer of polycarbonate and their mixtures with different molecular weight percentages of embedded single walled carbon nanotubes at different temperatures to study the structural and dynamical properties of the composite system. The diffusion behaviors of monomer, trimer of polycarbonate and carbon nanotubes in composite matrices are investigated and compared with pure matrices in details. Both structural and dynamical properties indicate the weak interaction between the nanotubes and matrix molecules. The high tendency of nanotubes to form bundles is observed during simulation. The bundle formation free energy has been calculated from the potential of mean force calculations. The mechanism and energetics of bundle formation is explored in the atomistic scale. The formation of the carbon nanotube bundle is a favorable process in the oligomeric polycarbonate matrix.

Structural and dynamical properties of polyethylenimine in explicit water at different protonation states: a molecular dynamics study - Choudhury, Chandan Kumar; Roy, Sudip (Soft Matter, 2013)
PEI is a pH sensitive polymer which acts as a proton sponge in acidic conditions. Despite many experimental and theoretical efforts, a fundamental understanding of the structure and dynamics of linear PEI chains on the atomistic level at different protonation states in dilute solutions remains a topic of discussion. This report analyses the structural properties of PEI at different protonation states, which are representative of different pH, using all atomistic molecular dynamic simulations. The structural properties revealed that the polymer at high pH (basic medium) is highly coiled, while at low pH (strong acidic conditions) the chains are elongated. We studied the dynamics and ordering of water molecules that are part of the solvation shells of the PEI chains at different protonation states. We observe that the water molecules are ordered along the polymer backbone for a completely protonated PEI chain (i.e. in the case of acidic pH) and hop to the neighbouring solvation shell. The residence time and the self-diffusion of water molecules in the solvation shells and their activation barriers were also calculated and analysed further. We concluded the study by correlating the solvation shell water dynamics and the structure of the PEI chain at different protonation states.

Self-assembly of phospholipids on flat supports - Mhashal, Anil R.; Roy, Sudip (Physical Chemistry Chemical Physics, 2015)
The current study deals with the self-assembly of phospholipids on flat supports using the Martini coarse grain model. We reported here the effect of the hydrophilic and hydrophobic nature of the solid supports on the lipid self-assembly. The hydrophilic and hydrophobic supports were modeled on the basis of water droplet simulations. The present work addresses the self-assembly mechanism of lipids on eight different supports with different strengths of hydrophilicity and hydrophobicity. We demonstrated how interplay between the interactions of lipid and water with the support can guide the lipid self-assembly process. Thereafter, we calculated the energetics of the components of the system to quantify the competitions between water and a lipid head-group with hydrophilic supports. Finally, the properties of the self-assembled bilayers were also analyzed and reported here.

Structure of nanorod assembly in the gyroid phase of diblock copolymer - Chakraborty, Souvik; Roy, Sudip (Journal of Physical Chemistry B, 2015)
Diblock copolymers undergo microphase separation to form various microstructures, for example, lamellar, gyroid, cylindrical, cubic phases depending on compostion and segregation strength (Flory-Huggins parameter chi). Thus, it can act as template to organize doped nanomaterials into different 3D self-assembled structures located within the block copolymer matrix. Gyroid phase is One of the microstructures formed by block copolymer. It has a curved interfacial surface providing confinements throughout the matrix and thus can regulate the shape and sizes of self-assembled nanorods doped in it. Mesoscale simulation of model systems has been performed to explore the structure and dynamics of self-assembly of bundles formed by nanorods of different flexibilities in the gyroid phase of diblock copolymer matrix. Bundles of different shapes and sizes have been found to be formed depending on the nanorod bending flexibility and copolymer-nanorod interactions. The shape anisotropy (kappa(2)) and radius of gyration (R-g(2)) of bundles situated at different interfacial confining locations of block copolymer-matrices have been investigated as a function of nanorod flexibility and nanorod-diblock copolymer miscibility.

Scalability of coarse-grained potentials generated from iterative boltzmann inversion forpolymers: case study on polycarbonates - Choudhury, Chandan Kumar; Carbone, Paola; Roy, Sudip (Macromolecular Theory and Simulations, 2016)
Using systematic coarse-grained (CG) techniques such as iterative Boltzmann inversion (IBI) is an efficient means to simulate high molecular weight polymer melts within reasonable computational time. One drawback of such an approach is however the need to carry out extensive atomistic simulations in order to extrapolate the necessary distributions to derive the inter and intrabead force field parameters. Here it is shown that it is possible to use atomistic simulations of relative short oligomers to develop the CG model for high molecular weight polymers. In particular for the specific case of polycarbonates, it is found that the structural properties (end-to-end distance, radius of gyration and their distributions) are similar irrespective of whether the CG potentials are derived from 5-mer or 10-mer melt systems. Dynamical properties of the CG systems are smoother and faster than the atomistic ones. Scaling factor, derived by overlapping the CG mean square displacement curves (obtained from different CG IBI potentials) over the atomistic ones, also scales the autocorrelation functions. A prediction of the dynamical scaling factor in the case of the unavailability of atomistic simulations is also discussed. The dynamical properties of the CG melts are modeled reasonably well by all the CG potentials derived from atomistic simulations of short oligomers.

Structural and conformational properties of polybenzimidazoles in melt and phosphoric acid solution: a polyelectrolyte membrane for fuel cells - Pahari, Swagata; Roy, Sudip (RSC Advances, 2016)
Poly[2,2'-(p-phenylene)-5,5'-bibenzimidazole (PBI) and poly(2,5-benzimidazole) (ABPBI) doped with phosphoric acid (PA) are considered as potential polymer electrolyte membranes for high temperature fuel cells. Conformational and structural properties of polymer chains in the presence of PA govern the function of the membrane. Therefore, in this work, a single chain conformational analysis of ABPBI and PBI in melt as well as in PA was performed using classical molecular dynamics simulations. End-to-end distance and the radius of gyration reveal significant changes in the conformations of PBI and ABPBI in PA. The structural changes are analyzed locally segment-wise as well as globally in these polymers. The shape and nature of the curvature along the chain is found to be significantly different for ABPBI and PBI. The role of the solvent (PA) on the chain backbone structure is explored for PA doped ABPBI and PBI chains. The PA arrangement along the backbone confirms that benzimidazole density in the case of both of the polymers determines the PA absorbing capacity. The H-bonding interactions between various atoms of the polymer backbone and the atoms of the PA molecules are evaluated along the polymer chain which relates to the arrangement of PA along the backbone. The reasons for the varying number of H-bonds along ABPBI and PBI which in turn has a significant effect on the stiffness of the chains are investigated.

Structural insight into self assembly of sophorolipids: a molecular dynamics simulation study - Pandey, Prithvi Raj; Dhasaiyan, Prabhu; Bhagavatula L. V. Prasad; Roy, Sudip (Zeitschrift Fur Physikalische Chemie-International Journal of Research in Physical Chemistry & Chemical Physics, 2016)
Sophorolipids contain hydrophilic head groups at the ends of a long hydrophobic tail. As a result, sophorolipids can self assemble into variety of structures in water. Atomistic self assembly simulations of sophorolipids are performed in water. Two sophorolipids, oleic acid sophorolipid and linolenic acid sophorolipid, differing in number of double bonds in the hydrophobic tail are considered for this study. Long time self assembly simulations are performed considering 1 :3 lipid to water ratio by weight for both oleic and linolenic acid sophorolipids. In addition to 1 : 3 ratio, long time self assembly simulations are also performed with 1 : 1 and 1 : 2 ratios for linolenic acid sophorolipids. Distinctions in structural arrangements of sophorolipid molecules in the self assembled configuration for all the systems are investigated. The present study aims to provide structural insight into the different self assembled configurations of sophorolipids in water.
Keywords: MD Simulation; self assembly; sophorolipids; United Atom Force Field

Self-exfoliated guanidinium-based ionic covalent organic nanosheets (iCONs) - Mitra, Shouvik; Kandambeth, Sharath; Biswal, Bishnu P.; Khayum, Abdul M.; Choudhury, Chandan Kumar; Mehta, Mihir R.; Kaur, Gagandeep; Banerjee, Subhrashis; Prabhune, Asmita; Verma, Sandeep; Roy, Sudip; Kharul, Ulhas K.; et al. (Journal of the American Chemical Society, 2017)
Covalent organic nanosheets (CONs) have emerged as functional two-dimensional materials for versatile applications. Although pi-pi stacking between layers, hydrolytic instability, possible restacking prevents their exfoliation on to few thin layered CONs from crystalline porous polymers. We anticipated rational designing of a structure by intrinsic ionic linker could be the solution to produce self-exfoliated CONs without external stimuli. In an attempt to address this issue, we have synthesized three self-exfoliated guanidinium halide based ionic covalent organic nanosheets (iCONs) with antimicrobial property. Self-exfoliation phenomenon has been supported by molecular dynamics (MD) simulation as well. Intrinsic ionic guanidinium unit plays the pivotal role for both self-exfoliation and antibacterial property against both Gram-positive and Gram-negative bacteria. Using such iCONs, we have devised a Mixed matrix membrane which could be useful for antimicrobial coatings with plausible medical benefits.